Evaluación de cuatro soluciones nutritivas con fertigación para el cultivo de tomate indeterminado bajo invernadero - Paladines Jumbo, César Manuel (2008)
The present investigation on the evaluation of four nutritious solutions for indetermine tomato with fertigación under conservatory was made in the experimental farm Santa Ines of the Faculty of Farming Sciences of the Technical University of Machala, located in the parish the Change, and their objectives were: 1. To evaluate four nutritious solutions for indetermine tomato with fertigación under conservatory; to 2.Determinar the best nutritious solution from the economic point of view. and 3. To establish the yield of the culture. The area used for the test was of 42 m², under conservatory cover; the beds had 1,60 ms of length by 0,90 wide ms of and one height of 0.40 ms; the irrigation occurred by dripping incorporating the fertilizer through a Venturi measurer. Four treatments studied completely, using a random design, for the T1 (witness) was used the recommendation of the FAO, the T2 went 25% minor to the T1, the T3 had a greater concentration 25 % to the witness, and the T4 was equal to the T1 as far as nitrogen, phosphorus and potassium but 25 % greater in calcium and magnesium. The variance analyses, gave like result that was no statistical difference for treatments in height of plant, length of horizontal and vertical the fruit and diameters, but the description agronomics in days to the flowering, flowers by Bouquet, fruits by Bouquet, weight of the fruit and yield by hectare presented/displayed statistical difference. Of the nutritious solutions evaluated the best one she was the one of the T4 treatment (equal to witness but 25 % in calcium and magnesium) surpassing to the yield of the witness in a 27 %. By means of the economic, single analysis the T4 treatment turned out to be profitable in the first harvest made to the 5 months, but projecting to two years that are the cycle of culture of this variety, all the treatments turn out to be profitable.